“Tipos de evaluación en el proceso de enseñanza-aprendizaje” - Chuqui Saquinga, Senaida Vanesa (2023)
In this research project, we studied the types of evaluation in the teaching-learning process, which allowed us to identify the learning progress of students, making it possible to remedy the shortcomings that occur at the learning level, in addition, to evaluate more than being the means to obtain quantitative grades is considered as a process that takes place at the same time with the PEA, whose application is before, during and after. The objective was to analyze how the types of evaluation affect the teaching-learning process of seventh grade students of the "Canada" Educational Unit, Latacunga canton, Cotopaxi province, school year 2022-2023. The methodology was based on the qualitative approach, applying the types of field and documentary research, since it studies the phenomena in their natural environment, the design was based on content analysis, also, the theoretical method was inductive. The techniques used were: observation and interview; with their respective instruments, allowing the collection of information from the subjects involved in the research. As for the results, it was mentioned that it is important to apply each type of evaluation in the established time to contribute to the PEA, therefore, as a proposal, interactive evaluation cards were designed in order to improve the evaluation process for the students. Finally, this project contributed to the analysis of the influence of the different types of evaluation used by teachers in school activities.